Implementasi Program Rehabilitasi dan Rekonstruksi Pasca Bencana Banjir di Nagari Ganting Mudiak Utara Surantih Kecamatan Sutera Kabupaten Pesisir Selatan - Putra, Irsan Rahmat; Mubarak, Adil (YASIN, 2025)
Post flood rehabilitation and reconstruction programs in various regions often face challenges in their implementation, yet in depth studies at the nagari level remain limited. This study aims to analyze the implementation of post disaster rehabilitation and reconstruction programs in Nagari Ganting Mudiak Utara, Sutera Subdistrict, Pesisir Selatan Regency. A descriptive qualitative approach was used, with participants including nagari officials, representatives from the Regional Disaster Management Agency (BPBD), and affected community members. Data were collected through interviews, observation, and documentation, then analyzed using data reduction, data presentation, and conclusion drawing techniques. The results show that the rehabilitation program includes social, psychological, and economic recovery, with high community participation. However, limited facilities and human resources are the main obstacles. Meanwhile, the reconstruction program focused on rebuilding basic infrastructure such as roads, bridges, and residents' homes, which was carried out gradually by the local government. Budget constraints and bureaucratic processes slowed down its implementation. The conclusion of this study is that although the program has shown positive outcomes, more comprehensive planning, strengthened interagency coordination, and enhanced implementation capacity are needed so that post disaster response efforts can be more effective, efficient, and sustainable.